Pelatihan dan Pengembangan Aplikasi Akuntansi MYOB Accounting pada Sekolah Menengah Kejuruan Swasta (SMKS) Medan Area – 1 - Abdul Gani gani; Minasari Nasution; Emilia Embun Sari; Yuniar Andi Astuti; Miftah Faridh Nasir (Pelita Masyarakat, 2023)
This service activity is part of the contribution of the Politeknik Unggul LP3M. in an effort to increase, enrich and provide knowledge about the basic theory of accounting and about self-potential, especially in the field of using accounting applications, namely using the MYOB (Mind Your Own Business) application, This training was conducted in order to provide preparation for students in the Ujian Kompetensi Keahlian (UKK) in the form of assignments, namely completing the Trading Company Accounting Cycle by operating the Accounting Application (MYOB). The problem at this service is that students do not have adequate knowledge and skills in operating the application. The ability to enter accounting transactions to present financial reports in accounting applications is one of the competencies that must be possessed by every SMK student in the accounting field. Implementation by demonstrating the myob accounting application then guiding students in its implementation. the community service team presented related material then continued with methods and questions and answers. the benefits that students get are being able to operate the myob accounting application to make financial reports so that it is a provision for working on the Accounting vocational competency exam.